A cycloartenol synthase from the steroidal saponin biosynthesis pathway of Paris polyphylla. Issue 4 (3rd April 2021) - Guo, Si-Yuan; Yin, Yan; Lei, Tao; Shi, Ying-Hui; Gao, Wei; Zhang, Xia-Nan; Li, Jia
Abstract: Steroidal saponins named polyphyllin are the major active components of Paris polyphylla . Cycloartenol synthase (CAS) is a key enzyme that catalyzes the formation of the sterol scaffold. In this study, we cloned a putative CAS gene from Paris polyphylla . Heterologous expression in yeast indicated that PpCAS can convert 2, 3-oxidosqualene into cycloartenol. qRT-PCR analysis showed that the expression of PpCAS was highest in leaves and lowest in roots. To our best knowledge, this is the first report of the functional characterization of cycloartenol synthase from Paris polyphylla, which lays the foundation for further analysis of the biosynthesis pathway of polyphyllins.